Pengaruh Konsep Diri dan Komunikasi Interpersonal terhadap Hasil Belajar PAI-BP Siswa Kelas VIII SMP N 2 Juwana Pati - Dwi Yunitasari; Dayyu Ariana Santoso; Karnadi (Al-Munawwarah : Jurnal Pendidikan Islam, 2022)
This study discussed the influence of self-concept and interpersonal communication on the learning outcomes of Islamic Religious Education and Characteristics (PAI-BP) of 8thclass students of SMP N 2 Juwana. The purpose of this study was to examine the effect of self-concept and interpersonal communication on learning outcomes of PAI-BP. This research is a quantitative study using multiple linear regression analysis. The Data was collected by using simple random sampling survey with the sample 152 and population 245 students of 8th class. The data collection technique was questionnaire method and a written test. The results of multiple linear regression analysis show that there was a significant influence between self-concept and interpersonal communication on the learning outcomes of PAI-BP and the coefficient of determination was 0.625. The coefficient of determination showed that the regression model represented 62,5% of data variance, and 37.5% was represented by other variables outside the regression model.